Advances in Computing and Communications, Part III First International Conference, ACC 2011, Kochi, India, July 22-24, 2011. Proceedings, Part III - Abraham, Ajith; Lloret Mauri, Jaime; Buford, John; Suzuki, Junichi; Thampi, Sabu M. (Communications in Computer and Information Science, 2011)
This volume is the third part of a four-volume set (CCIS 190, CCIS 191, CCIS 192, CCIS 193), which constitutes the refereed proceedings of the First International Conference on Computing and Communications, ACC 2011, held in Kochi, India, in July 2011. The 70 revised full papers presented in this volume were carefully reviewed and selected from a large number of submissions. The papers are organized in topical sections on security, trust and privacy; sensor networks; signal and image processing; soft computing techniques; system software; vehicular communications networks.